Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I want to find the number $a$ and $b$ such that $\lim_{x\to 0} \frac{\sqrt{ax+b}-2}{x}=1$.

First of all, I know that $b$ has to be 4, because the limit of the numerator has to be zero because the denominator is zero when we take its limit.

My problem is with the number $a$. I need help.

Thanks a lot!

share|cite|improve this question
@Amzoti $a$ and $b$ need to be numbers, i.e. constants, i.e. independent of $x$. – Fly by Night Jan 30 '13 at 20:22
up vote 6 down vote accepted

Multiplying by the conjugate gives: $$ \frac{\sqrt{ax+b}-2}{x}=\frac{ax+b-4}{x(\sqrt{ax+b}+2)}. $$

As you already observed, you need $b=4$, for otherwise the limit is infinite. Then you can simplify by $x$.

Now the limit is: $$ \frac{a}{\sqrt{4}+2}=\frac{a}{4}. $$

So you want $a=4$.

share|cite|improve this answer

As $x\rightarrow 0$, the square root behaves as $$\sqrt{ax+b}=\sqrt{b}\sqrt{1+\frac{a}{b}x} \sim \sqrt{b}\left(1+ \frac{1}{2}\frac{a}{b}x+O(x^2)\right).$$ Subtracting the $2$ and dividing by $x$, we have $$ \frac{\sqrt{ax+b}-2}{x}\sim\frac{\sqrt{b}-2}{x}+\frac{a}{2\sqrt{b}}+O(x). $$ For the first (diverging) term to vanish, you need $b=4$; to make the second (constant) term equal to $1$, you also need $a=4$.

share|cite|improve this answer

When $a=b=4$. We can calculate the binomial series of $\sqrt{ax+b}$ and we find that

$$\sqrt{ax+b} \sim \sqrt{b} + \frac{a}{2\sqrt{b}}x + \cdots$$

Using this approximation, we see that

$$\frac{\sqrt{ax+b}-2}{x} \sim \frac{\sqrt{b}-2}{x} + \frac{a}{2\sqrt{b}} + \cdots $$

where the tail "$+\cdots$" consists of terms divisible by $x$. Assuming that $\sqrt{b} \neq 2$, the limit is undefined as $x \to 0$. If $\sqrt{b} = 2$, i.e. $b=4$ then we have:

$$\frac{\sqrt{ax+4}-2}{x} \sim \frac{a}{4}-\frac{a^2}{64}x + \cdots $$

where the tail "$+\cdots$" consists of terms divisible by $x^2$. In this case, the limit as $x \to 0$ is $\frac{1}{4}a$ and so we need $a=4$. It follows that

$$\lim_{x \to 0}\left(\frac{\sqrt{4x+4}-2}{x}\right) = 1 \, . $$

share|cite|improve this answer
Except when $b=4$. – 1015 Jan 30 '13 at 20:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.